THE FORMATION OF A PEDAGOGICAL CULTURE OF FUTURE SPECIALISTS AS A PRESSING PEDAGOGICAL ISSUE (Physical Culture and Sport: Scientific Perspective, 2023)
The article substantiates that modernization of the educational system at all levels is one of the most important directions of modern state educational policy. The central place in the reformation of higher education is occupied by ensuring and improving the quality of the educational process. These are both the goals and the results of each higher education institution’s activities. Modern higher education in Ukraine is a central social and state institution whose essential function is to prepare future specialists for various aspects of future activities in a specific field. The challenge of improving the quality of modern specialist’s; work depends on the development of a pedagogical culture. The solution to this problem is vital, first of all, since the formation of skills to solve professional challenges is a priority and more than obvious. This paper aims to analyze the phenomenon of the pedagogical culture of future specialists, as well as to determine the main directions of its formation in higher education institutions. Research goals: to analyze scientific research on the selected topic; to consider the existing positions of scientists on the phenomenon under study; to identify the main directions within which the formation of student’s; pedagogical culture takes place. A combination of interrelated research methods was employed to determine the theoretical framework of the studied phenomenon. These methods include analysis and synthesis, comparison, classification, and generalization of scientific approaches to the research problem presented in philosophical, sociological, psychological, and pedagogical sources. Research results. The pedagogical culture is seen as an integral feature that determines the ability of future specialists to solve professional issues and typical professional tasks that arise in real situations in their professional activities by using knowledge, professional and life-giving experience, values, and personal abilities. In general, the concept of "pedagogical culture" is associated with the creative development of people and their self-realization, professional self-improvement, and the cultural potential of a person. In this regard, the formation of a pedagogical culture is becoming increasingly important. It also becomes a critical factor in the professional and personal development of future specialists. The author has substantiated that the processes of education, upbringing, and professional formation of future specialists at the current stage are directly related to society’s attitude towards the values of pedagogical culture. The development and preservation of pedagogical culture is not only a condition for the effectiveness of the educational process but also an indicator of the viability of the education system itself. It has been determined that the formation of student’s; pedagogical culture is carried out during professional training in three main areas: during psychological and pedagogical training of students (the study of psychology, pedagogy); within the organization of student’s; self-activity aimed at developing and deepening theoretical knowledge and practical skills; during self-education and self-educational activities. The formation and development of pedagogical culture is a complex process that lasts for the entire professional life.
Keywords: professional culture; pedagogical culture; future specialists; professional training